Decompressive Laminectomy for Neurological Complications of Spondylodiscitis: A Case Series of 15 Patients - Andrea Bruno; Antonio Meola; Stefano Di Bella; Leonello Tacconi (Journal of Personalized Medicine, 2026)
Background/Objectives: Surgical indications for spondylodiscitis are controversial, particularly when epidural extension and evolving neurological compromise are present. This study aimed to describe the clinical, neurological, pain-related, and inflammatory outcomes of patients with spondylodiscitis treated with decompressive laminectomy without spinal stabilization, at a single tertiary center. Methods: We retrospectively reviewed 15 consecutive patients with spondylodiscitis who underwent decompressive laminectomy at the University Hospital of Trieste between January 2017 and December 2023. Inclusion required at least 6 months of clinical and laboratory follow-up. Patients treated with acute vertebral stabilization were excluded. Collected data included spinal level, timing from diagnosis to surgery, visual analog scale (VAS) pain score, Cooper Scale grade, modified Japanese Orthopedic Association score (mJOA), white blood cell count, and C-reactive protein (CRP). Assessments were performed preoperatively (T0), 1 week after surgery (T1), and at 6 months (T2). Imaging findings from representative cases were reviewed to illustrate the radiographic evolution after decompression combined with antibiotic therapy and orthotic support. Results: The cohort included 8 women and 7 men with a mean age of 57.33 years. Twelve patients (80%) underwent surgery within 48 h because of neurological deterioration or urgent compressive findings. Thoracic involvement was predominant (11 cases, 73%), whereas cervical and lumbar disease accounted for 1 and 3 cases, respectively. Intraoperative cultures were positive in 9 patients (60%), and Staphylococcus aureus was isolated in 7 of these 9 cases (77.8%). Mean VAS pain score improved from 6.3 at T0 to 4.3 at T1 and 1.4 at T2. Mean lower-extremity Cooper Scale grade improved from 2.7 to 2.1 to 0.6; mean upper-extremity Cooper Scale grade improved from 1.3 to 1.0 to 0. Mean mJOA improved from 10.3 to 11.4 to 16.0. Mean white blood cell count declined from 11.58 to 8.35 to 6.14 × 103/µL, and mean CRP declined from 123.9 to 72.81 to 19.44 mg/L. No patient worsened neurologically after surgery. No patient required acute stabilization or delayed arthrodesis during follow-up. Conclusions: In our case series of patients with compressive or progressive neurological spondylodiscitis, decompressive laminectomy combined with antibiotic treatment, bracing, and rehabilitation was associated with early neurological stabilization, substantial pain relief, and marked reduction in inflammatory markers, without subsequent need for instrumented stabilization. These data support the role of spinal decompression as part of a personalized, effective treatment strategy in patients with neurological decline.